Third Wave of Globalization and Post-colonial African Economy - Amune, Paul Azemata (ESUT JOURNAL OF SOCIAL SCIENCES, 2022)
In today’s contemporary world, there have been a lot of changes and shifts in thoughts, ideologies, and views. Nothing seems to remain constant forever. While globalization is not new, it has come across different changes and shifts even in modern times. This work explains the three waves of globalization, in brief, looks at the historical past of colonial impact on Africa. Then, moves on highlight how the African economy could learn from some peculiar cases of emerging countries with some shared similarities such as China, India, and Brazil. Furthermore, this work demonstrates that the African economy can take good advantage of the global market competition in advancing the continent forward from where it is today to provide a better experience for the African people. Applied is the Comparative Cost Advantage theory for a better understanding of how Africa can increase its integration to benefit more from the global market competition. Hopefully, Africa can take advantage of this third wave of globalisation, which seems very promising.